AN ERROR ANALYSIS ON RECOUNT TEXT WRITTEN BY THE EIGHTYEAR STUDENTS OF SMP NEGERI 2 JUWIRING KLATEN - TRIANINGSIH, ROHMAH ERFIN (2010)
This research paper studies: 1) kinds of errors, 2) the most dominant errors, 3) the difficulties faced by the students in writing recount text. The objectives of this research are: 1) identifying the kinds of errors, 2) identifying the dominant errors, 3) identifying the difficulties faced by the students in writing recount text. The researcher applies the descriptive qualitative method as a type of research. To collect the data, the writer uses students' work sheets. There were 30 students' work sheets. The result of this research shows that there are 3 result they are: 1) Omission (noun, verb, pronoun, adverb, auxiliary, conjunction, article, and to be), the total number of omission error is 156 errors or 41.23%, addition (noun, verb, pronoun, conjunction, and article) the total number of omission error is 33 errors or 8.71%, misformation ( noun, past form, word spelling, auxiliary, and article) the total number of omission error is 98 errors or 25.91%, and misordering ( verb, pronoun, conjunction, and sentences) the total number of omission error is 91 errors or 24.06%, the total number of errors are 3.78 errors or 99.91%. They also made the dominant errors in writing recount text. The students have dominant errors is omission errors 156 errors or 41.23%, but the sub-kinds of errors there are 4 errors are 4 dominant errors are 41 omission of to be or 10.84%, addition of article 11 or 2.91%, misordering past form is the also dominate errors are 62 errors or 16.40% and misformations of sentence are 39 errors or 10.31%. Based on this research the researcher also found the difficulties faced by the students in writing recount text made by second year students of SMP Negeri 2 Juwiring Klaten namely: knowledge background, vocabulary, Indonesian-English, teaching media, and developing well-form English sentence actually in past form.